Comprehensive development and testing of the ASIST-GBV, a screening tool for responding to gender-based violence among women in humanitarian settings. Issue 1 (December 2016) - Wirtz, A.; Glass, N.; Pham, K.; Perrin, N.; Rubenstein, L.; Singh, S.; Vu, A.
Abstract Background Conflict affected refugees and internally displaced persons (IDPs) are at increased vulnerability to gender-based violence (GBV). Health, psychosocial, and protection services have been implemented in humanitarian settings, but GBV remains under-reported and available services under-utilized. To improve access to existing GBV services and facilitate reporting, the ASIST-GBV screening tool was developed and tested for use in humanitarian settings. This process was completed in four phases: 1) systematic literature review, 2) qualitative research that included individual interviews and focus groups with GBV survivors and service providers, respectively, 3) pilot testing of the developed screening tool, and 4) 3-month implementation testing of the screening tool. Research was conducted among female refugees, aged ≥15 years in Ethiopia, and female IDPs, aged ≥18 years in Colombia. Results The systematic review and meta-analysis identified a range of GBV experiences and estimated a 21.4 % prevalence of sexual violence (95 % CI:14.9-28.7) among conflict-affected populations. No existing screening tools for GBV in humanitarian settings were identified. Qualitative research with GBV survivors in Ethiopia and Colombia found multiple forms of GBV experienced by refugees and IDPs that occurred during conflict, in transit, and in displaced settings. Identified forms of violence were combined into seven key items on the screening tool: threats of violence, physical violence, forced sex, sexual exploitation, forced pregnancy, forced abortion, and early or forced marriage. Cognitive testing further refined the tool. Pilot testing in both sites demonstrated preliminary feasibility where 64.8 % of participants in Ethiopia and 44.9 % of participants in Colombia were identified with recent (last 12 months) cases of GBV. Implementation testing of the screening tool, conducted as a routine service in camp/district hospitals, allowed for identification of GBV cases and referrals to services. In this phase, 50.6 % of participants in Ethiopia and 63.4 % in Colombia screened positive for recent experiences of GBV. Psychometric testing demonstrated appropriate internal consistency of the tool (Cronbach's α = 0.77) and item response theory demonstrated appropriate discrimination and difficulty of the tool. Conclusion The ASIST-GBV screening tool has demonstrated utility and validity for use in confidential identification and referral of refugees and IDPs who experience GBV.